A pole piece and its preparation method and semi-solid battery

By performing laser microstructure processing and solid electrolyte coating on the electrode surface of the semi-solid lithium-ion battery, the problems of poor interface contact and lithium dendrites during the battery cycle are solved, and higher fast charging capacity and longer cycle life are achieved.

CN119786511APending Publication Date: 2025-04-08ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411686052.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the circulation process, existing semi-solid lithium-ion batteries have problems such as poor interface contact, lithium dendrites and safety risks, which affect their service life and safety.

Method used

By using lasers to mark or punch microstructures on the surface of the positive and negative electrode sheets, and applying a solid electrolyte layer to the surface of the electrode sheets, it prevents microstructure corrosion, expands the electrode surface area, and improves fast charging capabilities.

Benefits of technology

It significantly improves the fast charging capability and cycle life of the battery, reduces the generation and safety risks of lithium dendrites, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786511A_ABST
    Figure CN119786511A_ABST
Patent Text Reader

Abstract

The present invention discloses a pole piece and a preparation method thereof and a semi-solid battery, which sequentially include a current collector, an active material layer coated on the surface of the current collector, and a solid electrolyte layer coated on the surface of the active material layer, wherein a microstructure is provided on the side of the active material layer away from the current collector, and the depth of the microstructure is greater than the thickness of the solid electrolyte layer. The positive and negative pole pieces are etched, marked or punched by laser, and microstructure processing is performed on the surface of the pole piece to achieve the expansion of the reaction area of ​​the electrode surface, improve the fast charging capability, and inhibit the generation of lithium dendrites. Most importantly, a solid electrolyte layer is coated on the surface of the pole piece, which can effectively prevent corrosion of the pole piece surface, protect the microstructure of the pole piece surface, improve the battery life and capacity retention rate at high rates, and extend the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid state batteries, and in particular to a positive electrode sheet, a negative electrode sheet and a preparation method thereof, as well as a semi-solid state battery prepared by using the positive electrode sheet and the negative electrode sheet. Background Art

[0002] At present, the market prospects of semi-solid batteries are good, and they are expected to be widely used in new energy vehicles, portable energy storage, drones, smart wearable devices and other fields in the future. In recent years, with the accelerated development of the new energy vehicle industry, consumers' requirements for vehicle range and energy density have continued to increase. Semi-solid batteries have excellent performance and will have broad application prospects in the field of new energy vehicles.

[0003] As the application of lithium batteries continues to expand, the market's requirements for their service life, safety, energy density, and endurance continue to increase. Semi-solid batteries have excellent performance and are relatively easy to produce, and are expected to be widely used in the field of new energy vehicles in the future. At present, my country's semi-solid battery industry is still in its development stage. With the continuous increase in R&D investment in the future, the development speed of my country's semi-solid battery industry will further accelerate.

[0004] Currently, semi-solid lithium-ion batteries have a low number of cycles and a short battery life. Due to the poor interface contact between the semi-solid electrolyte and the electrode material, lithium dendrites are generated during the battery cycle. Once crystallized, they may pierce the diaphragm, and the positive and negative electrodes are in direct contact, which can easily cause safety problems and affect safety and battery life.

[0005] Therefore, how to balance the safety performance, fast charging capability and cycle performance of semi-solid lithium-ion batteries is still a problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a pole piece, a preparation method thereof and a semi-solid-state battery, use a laser to perform microstructural processing of scribing or punching on the surface of the pole piece, and coat a solid electrolyte on the surface of the pole piece to prevent the microstructure on the surface of the pole piece from corrosion and falling off during the battery cycle, protect the microstructure on the surface of the pole piece, expand the reaction area of ​​the electrode surface, and improve the fast charging capability.

[0007] The technical solution adopted by the present invention to solve the above technical problems is:

[0008] A pole piece comprises a current collector, an active material layer coated on the surface of the current collector and a solid electrolyte layer coated on the surface of the active material layer in sequence, wherein a microstructure is arranged on a side of the active material layer away from the current collector, and the depth of the microstructure is greater than the thickness of the solid electrolyte layer.

[0009] The microstructure can be a geometric structure of parallel linear grooves, meshes, lattices, etc. The microstructure can reduce the interstitial tortuosity of the thick electrode at high charge / discharge rates and increase the lithium ion diffusion coefficient in the case of thick electrodes.

[0010] Preferably, the depth of the microstructure is 20% to 80% of the thickness of a single side of the pole piece, or / and the thickness of the solid electrolyte layer is 2 μm to 10 μm.

[0011] Preferably, the microstructure includes at least one of a wire groove and a slot hole.

[0012] Preferably, the width of the microstructure is 30% to 120% of its depth.

[0013] A method for preparing a pole piece, used for preparing the pole piece mentioned above, comprises the following steps:

[0014] S1, adding a positive electrode active material, a positive electrode conductive agent and a positive electrode binder into a first solvent and mixing them evenly to obtain a positive electrode slurry, coating the positive electrode slurry on the surface of a positive electrode current collector to form a positive electrode active material layer, and obtaining a positive electrode sheet to be processed;

[0015] S2, using laser to perform microstructural processing on the surface of the positive electrode sheet to be processed;

[0016] S3, adding a solid electrolyte and a binder into a second solvent and mixing them evenly to obtain a positive electrode solid electrolyte slurry, coating the positive electrode solid electrolyte slurry on the surface of the positive electrode active material layer with a microstructure, and then drying it in an oven to obtain a positive electrode sheet;

[0017] or

[0018] C1. Adding the negative electrode active material, the negative electrode conductive agent and the negative electrode binder into the third solvent and mixing them evenly to obtain a negative electrode slurry, coating the negative electrode slurry on the surface of the negative electrode current collector to form a negative electrode active material layer, and obtaining a negative electrode sheet to be processed;

[0019] C2. Use laser to perform microstructural processing on the surface of the negative electrode sheet to be processed;

[0020] C3. Add the solid electrolyte, negative electrode active material and electrolyte layer binder into the fourth solvent and mix them evenly to obtain a second solid electrolyte slurry. Coat the second solid electrolyte slurry on the surface of the negative electrode active material layer with a microstructure, and then dry it in an oven to obtain a positive electrode sheet.

[0021] By using laser etching to perform microstructural processing on the surface of the positive and negative electrode sheets, the surface area of ​​the electrode is significantly increased, thereby enhancing the electrochemical reaction rate and improving the fast charging capability. In addition, the microstructure on the electrode surface can guide the deposition path of lithium ions on the electrode surface, reduce the formation of dendrites, and reduce the risk of short circuits. Then a layer of solid electrolyte layer is coated on the surface of the electrode sheet to prevent the microstructure on the surface of the electrode sheet from corroding and falling off during the battery cycle, protect the microstructure on the surface of the electrode sheet, and expand the reaction area on the surface of the electrode to improve the fast charging capability; it can also inhibit the generation of lithium dendrites during the cycle process; in the case of thick electrodes, the void tortuosity of thick electrodes can be reduced at high charge / discharge rates, and the lithium ion diffusion coefficient can be increased; it can improve the battery life and capacity retention rate at high rates, extend the cycle life of the battery, and further expand the potential for commercial application of semi-solid batteries.

[0022] Preferably, the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, ternary positive electrode active material and lithium manganese oxide; the positive electrode conductor is selected from at least one of conductive carbon black SP, carbon nanotube CNT, carbon nanofiber and graphene; the positive electrode binder is selected from at least one of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF and styrene-butadiene rubber SBR.

[0023] Preferably, the negative electrode active material is selected from at least one of graphite, silicon-carbon material, silicon and silicon-oxygen materials; the negative electrode conductive agent is selected from at least one of conductive carbon black SP, acetylene black, Ketjen black, carbon dots, carbon nanotubes CNT, graphene, carbon nanofibers, and superconducting carbon; the negative electrode binder is selected from at least one of styrene-butadiene rubber SBR, polyacrylic acid, and carboxymethyl cellulose CMC.

[0024] Preferably, the solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, a halide solid electrolyte or lithium nitride; the electrolyte layer binder is selected from one or more of styrene-butadiene rubber, nitrile rubber, ethyl cellulose, polyvinylidene fluoride, and polyacrylate, and the mass fraction of the binder in the solid electrolyte layer is 2% to 10%.

[0025] Preferably, the negative electrode active material is lithium titanate or carbon material, and the mass fraction of the negative electrode active material in the solid electrolyte layer is 10% to 20%.

[0026] A semi-solid battery comprises a positive electrode sheet and / or a negative electrode sheet prepared by the above-mentioned electrode sheet preparation method.

[0027] Compared with the prior art, the advantages of the present invention are:

[0028] 1. Since the surface microstructure of the electrode is very easy to corrode and fall off during the battery cycle, which affects the surface microstructure of the battery and the battery performance, by using laser-etched positive and negative electrode plates and coating a solid electrolyte layer on the surface of the electrode plate, the surface microstructure of the electrode plate is protected to prevent corrosion. The microstructure of the electrode surface has expanded the surface contact area compared with the original electrode, and the infiltration time with the semi-solid electrolyte is greatly shortened, thereby limiting the flow of electrolyte inside the electrode, inhibiting the side reactions of the electrolyte and the surface of the electrode material, and promoting the formation of a dense and complete protective film on the electrode surface. The protective film can reduce the loss of active lithium, thereby ensuring the excellent rate performance and cycle performance of the battery, improving the battery life and capacity retention rate at high rates, and extending the cycle life of the battery.

[0029] 2. The reaction area of ​​the electrode surface is expanded through microstructure, which effectively improves the fast charging capability and inhibits the formation of lithium dendrites. In the case of thick electrodes, the void tortuosity of the thick electrodes is reduced at high charge / discharge rates, thereby increasing the lithium ion diffusion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet in the present invention;

[0032] Figure 2 It is a schematic diagram of the structure of the negative electrode sheet in the present invention;

[0033] Figure 3 This is the SEM image of the surface microstructure of the positive electrode laser etching + solid electrolyte layer in Example 1;

[0034] Figure 4 This is a schematic diagram of the structure of the battery after lamination in Example 1;

[0035] Figure 5 This is the SEM image of the surface microstructure of the negative electrode laser etching + solid electrolyte layer in Example 2;

[0036] Figure 6 This is a schematic diagram of the structure of the battery after lamination in Example 2;

[0037] Figure 7 This is a schematic diagram of the structure of the battery after lamination in Example 3;

[0038] Figure 8This is a schematic diagram of the structure of the battery after lamination in Comparative Example 1;

[0039] Fig. 9 This is a schematic diagram of the structure of the battery after lamination in Comparative Example 2;

[0040] Fig.10 A schematic diagram of a geometric structure in which the surface microstructure of the positive electrode sheet of a laser-etched + solid electrolyte layer is parallel in the present invention;

[0041] Fig.11 This is a schematic diagram of a cross-shaped geometric structure of the surface microstructure of the laser-etched + solid electrolyte layer negative electrode plate proposed in the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0043] Example

[0044] A semi-solid-state battery is prepared by the following steps:

[0045] Step 1: Prepare the positive electrode plate: add the positive electrode active material, positive electrode adhesive, and positive electrode conductive agent into the first solvent and mix to obtain positive electrode slurry; add the solid electrolyte and electrolyte layer binder into the second solvent and mix to obtain positive electrode solid electrolyte slurry; apply the positive electrode slurry on the surface of the positive electrode collector to form a positive electrode active material layer to obtain the positive electrode plate to be processed; use laser to perform surface microstructure processing on the positive electrode plate; the depth of the processed microstructure is 20% to 80% of the thickness of the single side of the plate; the width of the microstructure is 30% to 120% of the depth; the microstructure can be a geometric structure such as parallel linear grooves, meshes, grids, slots, etc.; apply the positive electrode solid electrolyte slurry on the surface of the plate; the thickness of the positive electrode solid electrolyte layer coating is 2μm to 10μm; and after drying in an oven, the positive electrode plate is obtained. Figure 1 shown.

[0046] The positive electrode current collector may be selected from a metal foil or a composite current collector, for example, an aluminum foil. The positive electrode active material is selected from at least one of lithium cobalt oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, ternary positive electrode active materials and lithium manganate. The positive electrode conductive agent is selected from at least one of conductive carbon black SP, carbon nanotube CNT, carbon nanofiber and graphene. The positive electrode adhesive is selected from at least one of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF and styrene-butadiene rubber SBR.

[0047] The solid electrolyte is selected from at least one of sulfide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte, halide solid electrolyte or lithium nitride. The electrolyte layer binder is selected from one or more of styrene-butadiene rubber, nitrile rubber, ethyl cellulose, polyvinylidene fluoride and polyacrylate, and the mass fraction of the binder in the solid electrolyte layer is 2% to 10%.

[0048] Step 2: Prepare the negative electrode sheet: add the negative electrode active material, negative electrode binder and negative electrode conductive agent into the third solvent and mix to obtain negative electrode slurry; mix the solid electrolyte, negative electrode active material and electrolyte binder to obtain negative electrode solid electrolyte slurry; apply the negative electrode slurry on the surface of the negative electrode collector to form a negative electrode active material layer to obtain the negative electrode sheet to be processed; use laser to perform surface microstructure processing on the negative electrode sheet; the depth of the processed microstructure is 20% to 80% of the thickness of the single side of the sheet; the width of the microstructure is 30% to 120% of the depth; the microstructure can be parallel, mesh, grid, slot and other geometric structures; apply the negative electrode solid electrolyte slurry on the surface of the sheet; the thickness of the negative electrode solid electrolyte layer coating is 2μm to 10μm; after drying in an oven, the negative electrode sheet is obtained. Figure 2 shown.

[0049] The negative electrode active material is selected from at least one of graphite, silicon-carbon material, silicon and silicon-oxygen materials. The negative electrode conductive agent is selected from at least one of conductive carbon black SP, acetylene black, Ketjen black, carbon dots, carbon nanotubes CNT, graphene, carbon nanofibers, and superconducting carbon. The negative electrode binder is selected from at least one of styrene-butadiene rubber SBR, polyacrylic acid, and carboxymethyl cellulose CMC.

[0050] The solid electrolyte is selected from at least one of sulfide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte, halide solid electrolyte or lithium nitride; the electrolyte layer binder is selected from one or more of styrene-butadiene rubber, nitrile rubber, ethyl cellulose, polyvinylidene fluoride, polyacrylate, and the mass fraction of the binder in the solid electrolyte layer is 2% to 10%. The negative electrode active material is lithium titanate or carbon material, and the mass fraction of the negative electrode active material in the solid electrolyte layer is 10% to 20%.

[0051] ③ Prepare the negative electrode sheet, separator, positive electrode sheet and shell into a dry battery cell;

[0052] ④ Inject the semi-solid electrolyte into the dry battery cell and let it stand. The purpose of the wetting is to allow the electrolyte to completely wet the laser-etched positive and negative electrode sheets, thereby providing a transmission channel for ions between the positive and negative electrode sheets and expanding the reaction area on the electrode surface;

[0053] ⑤ After standing still, the battery cell is subjected to formation and capacity separation to make the polymerizable small molecule monomers undergo polymerization reaction to form a semi-solid lithium-ion battery.

[0054] In some optional embodiments, the semi-solid electrolyte can be mixed with acetonitrile electrolyte by selecting at least one of polyethylene glycol, tetraethyl orthosilicate, bis(diazacyclic) crosslinking agent and the like. The positive and negative electrode sheets etched by laser can withstand high voltage and are suitable for the needs of high-rate batteries.

[0055] The positive and negative electrode plates designed by laser etching described in this application use laser to perform microstructure processing on the positive and negative electrode plates, and coat a solid electrolyte layer on the surface of the plate to prevent corrosion on the surface of the plate, protect the microstructure on the surface of the plate, expand the reaction area on the electrode surface, improve the fast charging capability, and slightly increase the battery capacity; the microstructure forms a capillary shape to shorten the wetting time, improve the wetting consistency, enhance the electrolyte wettability of the battery electrode and reduce the electrode tortuosity. The synergistic effect of enhanced wettability and reduced electrode surface tortuosity allows the microstructure on the surface of the battery plate to inhibit the generation of lithium dendrites and extend the cycle life. Combined with the physical model to analyze the wettability, it is shown that laser etching of any electrode can significantly improve the wetting and rate performance.

[0056] Embodiment 1,

[0057] This embodiment provides a method for preparing a semi-solid-state battery, including matching a positive electrode sheet (laser etching + solid electrolyte layer) + a negative electrode sheet.

[0058] Step 1: Photolithography + preparation of the positive electrode sheet of the solid electrolyte layer:

[0059] The ternary positive electrode material (NCM613), conductive carbon black (SP), carbon nanotubes (CNT), and positive electrode binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 96.5:1:0.8:1.5 to form a uniform positive electrode slurry. The oxide solid electrolyte and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 97.5:2.5 to form a uniform positive electrode solid electrolyte slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain the positive electrode plate to be processed. The surface microstructure of the positive electrode plate is processed by laser. The depth of the processed microstructure is ≈60μm (75% of the single-sided thickness), the width of the microstructure is ≈35μm (58% of the depth), and the surface microstructure of the positive electrode plate is a parallel geometric structure; the laser-etched positive electrode plate is obtained, and the solid electrolyte slurry is coated on the etched plate with a coating thickness of 4μm, and dried in an oven to obtain the positive electrode plate. As shown in the attached Figure 3 shown.

[0060] Step 2: Preparation of negative electrode sheet:

[0061] The negative electrode active material graphite, the binder carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and the conductive agent carbon black (SP) are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 96:1.5:1.5 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0062] ③Preparation of semi-solid-state batteries:

[0063] The laser-etched positive and negative electrodes are die-cut into the designed shapes respectively, and then stacked in sequence by a stacking machine in the form of negative electrode sheet-diaphragm-laser-etched positive electrode sheet-diaphragm-negative electrode sheet-…-diaphragm laser-etched positive electrode sheet-diaphragm-negative electrode sheet-diaphragm to form a core, and then transferred to the aluminum-plastic film punching pit after cold pressing and compaction, and then the top side is heat-sealed to obtain a dry battery cell, and then the semi-solid electrolyte is injected into the battery cell, left to stand for 6 hours, and a semi-solid battery is obtained after chemical formation and other processes. Among them, the cold pressing pressure is 5-10MPa, and the cold pressing time is: 10-60s; as shown in the attached Figure 4 shown.

[0064] Embodiment 2,

[0065] This embodiment provides a method for preparing a semi-solid-state battery, including matching a positive electrode sheet + a negative electrode sheet (laser etching + solid electrolyte layer).

[0066] Step 1: Preparation of positive electrode:

[0067] The ternary positive electrode material (NCM613), conductive carbon black (SP), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 96.5:1:0.8:1.5 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.

[0068] Step 2: Laser etching + preparation of the negative electrode sheet of the solid electrolyte layer:

[0069] The negative electrode active material graphite, the binder carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and the conductive agent carbon black (SP) are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 96:1.5:1.5:1 to form a uniform negative electrode slurry, and the oxide solid electrolyte, the negative electrode active material graphite and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 86.5:10:3.5 to form a uniform negative electrode solid electrolyte slurry. The positive electrode slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain the negative electrode sheet to be processed. The surface microstructure of the negative electrode sheet is processed by laser. The depth of the processed microstructure is ≈50μm (50% of the single-sided thickness), and the width of the microstructure is ≈45μm (90% of the depth). The surface microstructure of the negative electrode sheet is a parallel geometric structure, thereby obtaining a laser-etched negative electrode sheet. The solid electrolyte slurry is coated on the etched sheet with a coating thickness of 5μm, and dried in an oven to obtain the negative electrode sheet. As shown in the attached Figure 5 shown.

[0070] Step 3: Preparation of semi-solid-state battery:

[0071] The laser-etched negative electrode sheet and positive electrode sheet are die-cut into the designed shape respectively, and then the stacking machine is used to stack the sheets in the manner of laser-etched negative electrode sheet-diaphragm-positive electrode sheet-diaphragm-laser-etched negative electrode sheet-...-positive electrode sheet-diaphragm-laser-etched negative electrode sheet-diaphragm to form a pole core, and then after cold pressing and compaction, it is transferred to the aluminum-plastic film punching pit, and then the top side is heat-sealed to obtain a dry battery cell, and then the semi-solid electrolyte is injected into the battery cell, and it is left to stand for 6 hours. After the formation process, a semi-solid battery is obtained. Among them, the cold pressing pressure is 5-10MPa, and the cold pressing time is: 10-60s; as shown in the attached Figure 6 shown.

[0072] Example 3: This example provides a method for preparing a semi-solid-state battery, including matching a positive electrode sheet (laser etching + solid electrolyte layer) + a negative electrode sheet (laser etching + solid electrolyte layer).

[0073] Preparation of semi-solid-state batteries:

[0074] The positive electrode sheet (laser etching + solid electrolyte layer) in Example 1 and the negative electrode sheet (laser etching + solid electrolyte layer) in Example 2 are die-cut into the designed shapes respectively, and then stacked in sequence by a stacking machine in the manner of laser-etched negative electrode sheet - diaphragm - laser-etched positive electrode sheet - diaphragm - laser-etched negative electrode sheet - ... - laser-etched positive electrode sheet - diaphragm - laser-etched negative electrode sheet - diaphragm to form a pole core, and then transferred to the aluminum-plastic film punching pit after cold pressing and compaction, and then the top side is heat-sealed to obtain a dry battery cell, and then the semi-solid electrolyte is injected into the battery cell, left to stand for 6 hours, and a semi-solid battery is obtained after the formation process. Among them, the cold pressing pressure is 5-10MPa, and the cold pressing time is: 10-60s. As shown in the attached Figure 7 shown.

[0075] Comparative Example 1

[0076] Preparation of semi-solid-state batteries:

[0077] Battery cell assembly: The positive electrode sheet in Example 2 and the negative electrode sheet in Example 1 are die-cut into the designed shapes respectively, and then stacked in sequence by a stacking machine in the manner of negative electrode sheet - diaphragm - positive electrode sheet - diaphragm - negative electrode sheet - ... - positive electrode sheet - diaphragm - negative electrode sheet - diaphragm to form a core, and then transferred to the aluminum-plastic film punching pit after cold pressing and compaction, and then the top side is heat-sealed to obtain a dry battery cell, and then the semi-solid electrolyte is injected into the battery cell, left to stand for 6 hours, and a semi-solid battery is obtained after the formation process. Among them, the cold pressing pressure is 5-10MPa, and the cold pressing time is: 10-60s. As shown in the attached Figure 8 shown.

[0078] Comparative Example 2

[0079] Preparation of semi-solid-state batteries:

[0080] Cell assembly: The positive electrode sheet without solid electrolyte layer in Example 1 (laser etching) and the negative electrode sheet without solid electrolyte layer in Example 2 (laser etching) are die-cut into the designed shape respectively, and then stacked in sequence by a stacking machine in the manner of negative electrode sheet - diaphragm - positive electrode sheet - diaphragm - negative electrode sheet - ... - positive electrode sheet - diaphragm - negative electrode sheet - diaphragm to form a core, and then transferred to the aluminum-plastic film punching pit after cold pressing and compaction, and then the top side is heat-sealed to obtain a dry cell, and then the semi-solid electrolyte is injected into the cell, left to stand for 6 hours, and a semi-solid battery is obtained after the formation process. Among them, the cold pressing pressure is 5-10MPa, and the cold pressing time is: 10-60s; as shown in the attached Fig. 9 shown.

[0081] Battery performance test:

[0082] 25℃ cycle test, the test method is: in a 25±2℃ constant temperature box, the semi-solid battery is charged to 4.5V at 0.2C constant current and constant voltage, the cut-off current is 0.05C, and then discharged to 3V at 1C, and multiple charge and discharge cycles are performed under the above conditions. The capacity retention rate of the battery after 300 cycles is calculated, and each group has 5 batteries. The test results are averaged and recorded in Table 1.

[0083] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the first cycle (mAh) * 100%.

[0084]

[0085] Note: “√” indicates used, “×” indicates not used.

[0086] Combining the data of Examples 1, 2, 3 and Comparative Examples 1 and 2, it can be seen that the application of the semi-solid-state battery with the positive and negative electrode plate system using laser etching + solid electrolyte layer is significantly higher than the semi-solid-state battery without using the laser etching electrode system and the semi-solid-state battery with the laser etching electrode system. At the same time, its battery cycle capacity retention rate is better. It can be seen that the formed electrode surface microstructure can expand the reaction area of ​​the surface, and a layer of solid electrolyte is coated on the electrode plate surface microstructure, which is beneficial to reduce the side reaction of electrode plate surface corrosion during battery charging and discharging, improve the battery cycle performance, and increase the battery cycle life. At the same time, the generation of lithium dendrites in the battery cell is inhibited, and the battery cell safety is also improved to a certain extent.

[0087] In summary, the present invention provides a positive and negative electrode sheet designed by laser etching, a semi-solid battery and a preparation method and application thereof. The present invention uses laser to etch, mark or punch positive and negative electrode sheets, performs microstructure processing on the surface of the electrode sheet, and coats a solid electrolyte layer on the surface of the electrode sheet to prevent corrosion of the electrode sheet surface, protect the microstructure of the electrode sheet surface, expand the reaction area of ​​the electrode surface, improve the fast charging capability, and inhibit the generation of lithium dendrites. Through different positive and negative electrode sheet processing methods and matching, the contact area between the positive electrode sheet and the negative electrode sheet and the semi-solid electrolyte is effectively increased, thereby improving the electrochemical performance. In the case of thick electrodes, the void tortuosity of the thick electrodes is reduced at high charge / discharge rates, and the lithium ion diffusion coefficient is improved; the battery life and capacity retention rate at high rates can be improved, and the cycle life of the battery can be extended. The present invention has the advantages of simple operation, low cost and high efficiency, is suitable for industrial production, and has promotion and application value in the field of semi-solid battery technology.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A pole piece, characterized in that: The invention comprises a current collector, an active material layer coated on the surface of the current collector and a solid electrolyte layer coated on the surface of the active material layer in sequence. A microstructure is arranged on the side of the active material layer away from the current collector, and the depth of the microstructure is greater than the thickness of the solid electrolyte layer.

2. A pole piece according to claim 1, characterized in that: The depth of the microstructure is 20% to 80% of the thickness of a single surface of the pole piece, or / and the thickness of the solid electrolyte layer is 2 μm to 10 μm.

3. A pole piece according to claim 1, characterized in that: The microstructure includes at least one of a wire groove and a slot hole.

4. A pole piece according to claim 1, characterized in that: The width of the microstructure is 30% to 120% of the depth.

5. A method for preparing a pole piece, characterized in that: A method for preparing a pole piece according to any one of claims 1 to 4 comprises the following steps: S1, adding a positive electrode active material, a positive electrode conductive agent and a positive electrode binder into a first solvent and mixing them evenly to obtain a positive electrode slurry, coating the positive electrode slurry on the surface of a positive electrode current collector to form a positive electrode active material layer, and obtaining a positive electrode sheet to be processed; S2, using laser to perform microstructural processing on the surface of the positive electrode sheet to be processed; S3, adding a solid electrolyte and a binder into a second solvent and mixing them evenly to obtain a positive electrode solid electrolyte slurry, coating the positive electrode solid electrolyte slurry on the surface of the positive electrode active material layer with a microstructure, and then drying it in an oven to obtain a positive electrode sheet; or C1. Adding the negative electrode active material, the negative electrode conductive agent and the negative electrode binder into the third solvent and mixing them evenly to obtain a negative electrode slurry, coating the negative electrode slurry on the surface of the negative electrode current collector to form a negative electrode active material layer, and obtaining a negative electrode sheet to be processed; C2. Use laser to perform microstructural processing on the surface of the negative electrode sheet to be processed; C3. Add the solid electrolyte, negative electrode active material and electrolyte layer binder into the fourth solvent and mix them evenly to obtain a second solid electrolyte slurry. Coat the second solid electrolyte slurry on the surface of the negative electrode active material layer with a microstructure, and then dry it in an oven to obtain a positive electrode sheet.

6. A method for preparing a pole piece according to claim 5, characterized in that: The positive electrode active material is selected from at least one of lithium cobalt oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, ternary positive electrode active material and lithium manganese oxide; the positive electrode conductor is selected from at least one of conductive carbon black SP, carbon nanotube CNT, carbon nanofiber and graphene; the positive electrode binder is selected from at least one of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF and styrene-butadiene rubber SBR.

7. A method for preparing a pole piece according to claim 5, characterized in that: The negative electrode active material is selected from at least one of graphite, silicon-carbon material, silicon and silicon-oxygen materials; the negative electrode conductive agent is selected from at least one of conductive carbon black SP, acetylene black, Ketjen black, carbon dots, carbon nanotubes CNT, graphene, carbon nanofibers, and superconducting carbon; the negative electrode binder is selected from at least one of styrene-butadiene rubber SBR, polyacrylic acid, and carboxymethyl cellulose CMC.

8. A method for preparing a pole piece according to claim 5, characterized in that: The solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, a halide solid electrolyte or lithium nitride; the electrolyte layer binder is selected from one or more of styrene-butadiene rubber, nitrile rubber, ethyl cellulose, polyvinylidene fluoride, and polyacrylate, and the mass fraction of the binder in the solid electrolyte layer is 2% to 10%.

9. A method for preparing a pole piece according to claim 5, characterized in that: The negative electrode active material is lithium titanate or carbon material, and the mass fraction of the negative electrode active material in the solid electrolyte layer is 10% to 20%.

10. A semi-solid battery, characterized in that: It comprises a positive electrode sheet and / or a negative electrode sheet prepared by the electrode sheet preparation method according to claim 5.

Citation Information

Cited By

  • Negative pole piece, preparation method thereof and all-solid-state battery

    CN122025548A

  • Preparation method of ceramic layer protection type interface-free laminated semi-solid battery

    CN122781956A